Profiling of translational and rotational head accelerations in youth BMX with and without neck brace - Hurst, H. T.; Rylands, L.; Atkins, S.; Enright, K.; Roberts, S. J. (Journal of Science and Medicine in Sport, 2018)
OBJECTIVES: To investigate the influence of BMX helmets and neck braces on translational and rotational accelerations in youth riders. DESIGN: Mixed model, repeated measure and correlation. METHODS: Twenty three competitive youth BMX riders classified by age group (6-9 years, 10-13 years and 14-18 years) completed 6 laps of an indoor BMX track at race pace, 3 laps without a neck brace (NB) and 3 without brace (WB). A triaxial accelerometer with gyroscope was placed behind the right ear to determine the mean number of accelerations, translational and rotational, of the head between conditions and by age group. RESULTS: Significant reductions by condition (p=0.02) and by age (p=0.04) were found for the number of accelerations, though no interactions (condition×age) were revealed. Significant increases by age (p=0.01) were revealed for translational accelerations, whilst significant increases by condition (p=0.02) were found for rotational accelerations. In addition, significant correlations were revealed between relative helmet mass and age (r=0.83; p=0.001) and relative helmet mass and number of accelerations (r=0.46; p=0.03). CONCLUSIONS: Accelerations at the head decreased with increased age, possibly due to the influence of greater stabilising musculature. Additionally, neck braces also significantly reduced the number of accelerations. However, the magnitude of accelerations may be influenced by riding dynamics. Therefore, the use of neck braces combined with strength work to develop neck strength, could aid in the reduction of head accelerations in youth BMX riders.